2016
DOI: 10.1007/s10722-016-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

Raffinose family oligosaccharides in seeds of Pisum wild taxa, type lines for seed genes, domesticated and advanced breeding materials

Abstract: The content of raffinose family oligosaccharides (RFOs) in pea seeds constrains their usage in feeding humans and animals. In our research, the content of soluble carbohydrates-particularly a-Dgalactosides of sucrose (RFOs)-was analyzed. The materials were as follows: 248 accessions from the Polish Pisum Genebank including representatives of taxa (from species to convarietas), type lines for genes controlling seed characters, and breeding materials and cultivars. Accessions were divided into homogeneous groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Karner et al (2004) found a significant role of myo-inositol at elevated concentrations for the accumulation of higher amounts of RFOs in pea seeds. However, recessive mutations in main pea seed genes (R, A and I) seems to be more important for an increased content of RFOs (Gawłowska et al 2017). Among 248 accessions of pea (derived form Polish Pisum Genebank) the highest content of RFOs were stated for accessions with wrinkled seeds (r and rb genes), whereas the lowest content for seeds of the wild species P. fulvum Sibth.…”
Section: Sectionmentioning
confidence: 96%
“…Karner et al (2004) found a significant role of myo-inositol at elevated concentrations for the accumulation of higher amounts of RFOs in pea seeds. However, recessive mutations in main pea seed genes (R, A and I) seems to be more important for an increased content of RFOs (Gawłowska et al 2017). Among 248 accessions of pea (derived form Polish Pisum Genebank) the highest content of RFOs were stated for accessions with wrinkled seeds (r and rb genes), whereas the lowest content for seeds of the wild species P. fulvum Sibth.…”
Section: Sectionmentioning
confidence: 96%
“…Domesticated pea species and advanced breeding lines have been shown to contain lower levels of raffinose oligosaccharides compared to other groups, suggesting that previous selection by breeders has already favoured lines with lower concentrations of these compounds (Gawłowska et al . ).…”
Section: Starch and Sugarsmentioning
confidence: 97%
“…Raffinose oligosaccharides are sugar compounds associated with flatulence (Gawłowska et al 2017). The predominant raffinose oligosaccharides in pea seeds are raffinose, stachyose and verbascose.…”
Section: Starch and Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening of the composition and content of RFOs in the seeds of important legume species from gene banks enables the detection of genotypes or mutants with a reduced content of RFOs, useful for further breeding. Such studies have already brought results in soybean (Mozzoni et al 2013), chickpea (Gangola et al 2013), lentil (Tahir et al 2012) and pea (Gawłowska et al 2017) production. In soybean, low raffinose and low stachyose genotypes were found (Mozzoni et al 2013), but the content of RFOs can be modified not only by genetic but also by environmental factors.…”
Section: Introductionmentioning
confidence: 99%